1997 West Indies tour of Pakistan and the crisis in Caribbean cricket - McGowan, Winston ([The Author] [Georgetown]GY, 1998)
Seeks to place the tour of Pakistan and the current crisis in West Indian cricket in historical perspective, with a view to understanding the causes, character and consequences of the crisis and prerequisites for its resolve.